FRECUENCIA DE Brucella sp. EN PORCINOS, PROCEDENTES DE GRANJAS TECNIFICADAS Y NO TECNIFICADAS, BENEFICIADOS EN DOS MATADEROS DE LIMA - Farro R., Diana (2002)
The objective ofthis study was to determine the frequency of Brucella sp in pigs from well managed and poor managed farms ot the Lima valley, Peru. For this purpose, blood samples ofpigs from well managed (n = 222) and poor managed (n = 218) forms were collected at two slanghterhouses. Animals were of both sexes and older than 4 months of age. Antibodies against Brucella sp. were detected by the Rose Bengal test (RB) andComplementFixation (CF) test. The frecuencyof Brucella sp. was4.77 ± 1.81 % in the studied population. The frequency of Brucella sp. in well and poor managed pig farms were2.25 ± 1.47% (5/222) and 7.34± 3.34% (16/218)respectively, whenRB testwas used. However, only 2.75 + 1.76% (6/218) in poor managed farms had antibodies against Brucella sp when using the CF test. None of the animals from well managed farms resulted positive by CF test. This study indicate the presence of brucellosis in poor managed pigs farms, representing a risk for the pig industry and public health.